2014
DOI: 10.1002/pmic.201400012
|View full text |Cite
|
Sign up to set email alerts
|

Generating a detailed protein profile of Fasciola hepatica during the chronic stage of infection in cattle

Abstract: Fasciola hepatica is a trematode helminth causing a damaging disease, fasciolosis, in ruminants and humans. Comprehensive proteomic studies broaden our knowledge of the parasite's protein profile, and provide new insights into the development of more effective strategies to deal with fasciolosis. The objective of this study was to generate a comprehensive profile of F. hepatica proteins expressed during the chronic stage of infection in cattle by building on previous efforts in this area. The approach included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 73 publications
0
20
0
Order By: Relevance
“…Pro-530 teins found to be common in the tegument of different fluke spe-531 cies are presented inTable 3, together with certain properties of 532 each protein such as membrane association, surface localisation 533 and antigenicity in infected hosts. Detergent extraction of tegu-534 ment proteins of adult F. hepatica has also been reported, however 535 analysis of the data showed that this extract comprised few mem-536 brane proteins but rather consists of a number of known excretory-537 secretory proteins, presumably regurgitated from the fluke gut, or 538 cytoplasmic proteins(Haçariz et al, 2012(Haçariz et al, , 2014 Morphew et al, 539 2013). This confounds any clear interpretation of which proteins 540 in the extract are actually from the tegument.541 4.3.…”
mentioning
confidence: 86%
“…Pro-530 teins found to be common in the tegument of different fluke spe-531 cies are presented inTable 3, together with certain properties of 532 each protein such as membrane association, surface localisation 533 and antigenicity in infected hosts. Detergent extraction of tegu-534 ment proteins of adult F. hepatica has also been reported, however 535 analysis of the data showed that this extract comprised few mem-536 brane proteins but rather consists of a number of known excretory-537 secretory proteins, presumably regurgitated from the fluke gut, or 538 cytoplasmic proteins(Haçariz et al, 2012(Haçariz et al, , 2014 Morphew et al, 539 2013). This confounds any clear interpretation of which proteins 540 in the extract are actually from the tegument.541 4.3.…”
mentioning
confidence: 86%
“…These recent technological developments have allowed more in depth analysis of these two Fasciola species to further our understanding of fluke biology and how they infect and persist within their hosts. Several secretome data sets are available for both species (154)(155)(156)(157)(158), which for F. hepatica are being complimented by analysis of the exosome component of the secreted proteins (159,160) as well as glycan analysis of these proteins (161; Ravida et al, unpublished), allowing in depth analysis of those proteins directly interacting with the host. A complete set of transcriptomes from the life cycle stages present within the definitive host, ranging from metacercariae to mature adult flukes are now available, allowing analysis of the extensive differential expression that occurs within this host, particularly as the parasite migrates through the liver (36).…”
Section: Advances In -Omic Technology Will Help Fill the Gaps In Our mentioning
confidence: 99%
“…In order to analyse differences in protein expression in the course of the study, three serum samples at each time point for each treatment were obtained and the protein profiles of the serum samples were analysed by LC-MS/MS method [18][19][20]. Albumin depletion from serum samples was done with albumin depletion spin columns (Pierce, Thermo Scientific).…”
Section: Serum Proteomic Analysismentioning
confidence: 99%
“…Minimum 3 technical replicates for each sample were used for the analysis. The proteomic data was searched against a reviewed database [including protein sequences of Bos taurus and an internal standard (enolase, Saccharomyces cerevisiae; #P00924), obtained from UniProt (htpp://www.uniprot.org)] with previously described in silico parameters [19]. Quantitative differences of proteins at different time points were calculated using Progenesis LC-MS software V4.0 (Nonlinear Dynamics) [20].…”
Section: Serum Proteomic Analysismentioning
confidence: 99%